The L2-Effnet for Human Skin Disease Multiclass Classification - Kurnia Adi Cahyanto; Kusworo Adi; Catur Edi Widodo (Universitas KH. Abdul Chalim Mojokerto, 2026)
Skin diseases are common health problems that are often underestimated as most are mild and can be treated with over-the-counter medications, however, some types such as melanoma can be cancerous and deadly if not treated properly. Melanoma is caused by overexposure to ultraviolet light and has a 99% cure rate if diagnosed early, but decreases to 20% in advanced stages. In Indonesia, the uneven distribution of medical personnel and geographical challenges cause many cases of skin diseases not to be diagnosed well. This study develops a multi-class skin disease classification model using transfer learning by utilizing pre-trained models such as EfficientNetV2S to overcome data imbalance and improve accuracy. The dataset used is a combination of ISIC and Atlas Dermatology, which has been curated into 31 classes with a total of 3,399 samples, and data augmentation was performed to increase the sample size. The modified L2-EfficientNetV2S model showed a testing accuracy of 88.33%, higher than previous studies, demonstrating the potential of using deep learning in the early diagnosis of skin diseases to improve healthcare.